Предикат у структурі речення - Кононенко, Віталій Іванович; Магас, Наталія Мирославівна; Тимофєєва, Ірина Сергіївна; Семенюк, Оксана Антонівна; Мудрак, Яна Володимирівна; Кононенко, Ірина Віталіївна; Федурко, Оксана Миронівна; Коржак, Зоряна Зіновіївна; Пітель, Василь Іванович; Ковбанюк, Мар’яна Іванівна; Гургула, Орест Богданович; Гошилик, Володимир Богданович; et al. (Національна академія педагогічних наук України, 2010)
У монографії висвітлено теоретичні проблеми семантичної організації речення, визначення функцій предиката як його центрального компонента. На матеріалі різних семантичних типів предикатів і засобів їх репрезентації в умовах елементарного й складного речень простежено ресурси української мови у вираженні логіко-референційних відношень. Розрахована на науковців, викладачів і студентів вищих навчальних закладів.

The monograph consideres the problems of predication as a defining category of the sentences semantic structure. The place, role and functions of predicate as a central component of the predicate expression are defined in relations with other structural elements based on the valency and intentions theory. The study put the idea of propositional sentences, including the interaction of discourse and modes, defined typology of predicates taking into account both the parameters of their semantic and formal grammar structures. The study, performed in the Ukrainian language material with the stylistic features ascertainment of artistic, journalistic, scientific and business style, helpes show the specificity of actant predicate relations in the national language continuum. The necessity to transcend the individual expression verge and include analysis of a broader context involving discourse formations was predetermined by the research. The book is based on the achievements and investigations of both Ukrainian and foreign linguists’ modern scientific ideas. The general concept approach based on the works of N. Arutyunova, I. Vykcho¬vanets, M. Heidegger, K. Horodenska, N. Guyvanyuk, A. Vezhbytska, A. Zahnitko, N. Ivanytska, G. Zolotova, V. Kononenko, I. Kononenko, O. Melnychuk, O. Paducheva, V. Rusanivskii, Y. Stepanov, J.R. Searle, G. Frege, N. Chomsky, N. Shvedova and others is introduced in the study. However, the monograph co-authors not seldom express their own opinions on the most complex issues of sentences semantic structure and their components, which makes possible to claim theoretical trend of this research on the whole. The book consists of introduction and four parts, built in the ten-dency of individual studies. In the introduction the notion of the sentence predicate centric concept is substantiated, the problems of components interaction on the basis of predicates intentional-valence properties are described. The semantic types of predicates are determined, in particular the mental predicates, predicates of physical state, emotional state predicates and factive predicates are analyzed in the first part. The semantic structure of sentences with predicates of different forms of representaion, expressed by predicates with adjectival component, adverb in predicative function, predicate nominative function compo¬nents and elliptic sentences are argued in the second part. The third part is dedicated to sentences predicative semantics complications with such components as a secondary predicate verbal adverb meaning, modified syntactic structure with the Infinitive of purpose, stable verbal nominal compounds and prepositional-substantives complexes. The fourth part deals with semantic categorial predicate centre. The interval semantics, debitive predicates as semantic category and performative sentences in a logic-semantic aspect are considered in the final part.
Predicate in the Structure of the Sentence
Keywords: semantic and syntactic sentence structure; prepositional substantival complex (PSC); predicate; model; dual-core predicate system; objective; instrumental; causal semantics; temporal semantics; locative semantics